Safety of proline‐specific oligopeptidase as a novel food pursuant to Regulation (EC) No 258/97 - Turck, Dominique (EFSA J, 2017)
Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on proline‐specific oligopeptidase (Tolerase(®) G) as a novel food ingredient submitted pursuant to Regulation (EC) No 258/97 of the European Parliament and of the Council, taking into account the comments and objections of a scientific nature raised by Member States. The novel food is an enzyme preparation of prolyl‐oligopeptidase produced with a genetically modified Aspergillus niger self clone strain. The target population is the general adult population. The results from a bacterial reverse mutation test and of an in vitro chromosome aberration test did not indicate genotoxicity. The Panel considers that the reported effects observed in a 90‐day rat study are treatment‐related effects and can be attributed to the higher energy consumption by these animals. Taking into account the intended maximum use level for Tolerase(®) G, its daily consumption would correspond to 2,746 mg TOS/person or to 39.2 mg TOS/kg body weight (bw) per day, when considering a default body weight of 70 kg for an adult person. The margin between this value and the dose in the rats, which caused effects attributable to the excess energy intake, is approximately 45. Noting this margin, the Panel considers that it is unlikely that such effects would occur in human at the intended use levels. The Panel concludes that the NF, Tolerase(®) G, is safe for the intended use at the intended use level.